Nucleus-Targeted Photosensitizer Nanoparticles for Photothermal and Photodynamic Therapy of Breast Carcinoma - Liu, Jing (Int J Nanomedicine, 2021)
PURPOSE: The near-infrared fluorescent dye indocyanine green (ICG) has shown great potential in the photodynamic therapy (PDT) and photothermal therapy (PTT) of cancer. However, its disadvantages of instability in aqueous solution, short half-life, and non-targeting accumulation limit the effectiveness of ICG PDT/PTT. To overcome the disadvantages of ICG in tumor treatment, we designed PEGylated-human serum albumin (PHSA)-ICG-TAT. In this nanoparticle, PEG4000, the HSA package, and nuclear targeting peptide TAT (human immunodeficiency virus 1 [HIV-1]-transactivator protein) were used to improve the water solubility of ICG, prolong the life span of ICG in vivo, and target the nuclei of tumor cells, respectively. METHODS: The PHSA-ICG-TAT was characterized in terms of morphology and size, ultraviolet spectrum, dispersion stability, singlet oxygen and cellular uptake, and colocalization using transmission electron microscopy and dynamic light scattering, and fluorescence assay, respectively. Subsequently, the anti-tumor effect of PHSA-ICG-TAT was investigated via in vitro and in vivo experiments, including cell viability, apoptosis, comet assays, histopathology, and inhibition curves. RESULTS: The designed ICG-loaded nanoparticle had a higher cell uptake rate and stronger PDT/PTT effect than free ICG. The metabolism of PHSA-ICG-TAT in normal mice revealed that there was no perceptible toxicity. In vivo imaging of mice showed that PHSA-ICG-TAT had a good targeting effect on tumors. PHSA-ICG-TAT was used for the phototherapy of tumors, and significantly suppressed the tumor growth. The tumor tissue sections showed that the cell gap and morphology of the tumor tissue had been obviously altered after treatment with PHSA-ICG-TAT. CONCLUSION: These results indicate that the PHSA-ICG-TAT had a significant therapeutic effect against tumors.